Computational Thinking Analysis of 21st Century Professional Teacher Candidates In Solving Math Problems Viewed from The Four Foundations of CT - Saddam Al Aziz; Ahmad Fauzan; Helma Helma (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
Computational Thinking (CT) is a further development which is the latest innovation in mathematical problem-solving skills. Four foundations of CT make it easier for someone to solve problems effectively, efficiently, and optimally. This mixed methods research with an embedded design. Quantitative data were collected using tests and qualitative data through written interviews and an overview of the prospective teacher's thought processes in answering tests. The sample that became the research subject was selected using the purposive sampling method by selecting 28 pre-service teacher's mathematics in Professional Teacher Education (PTE) who attended CT lectures. The object of this research is the 4 CT foundations of prospective teachers in solving math problems. This study describes how CT skills solve problems. The test results show that the percentage of correct answers for each of the four CT foundations is more than 80%. It can be concluded that the knowledge and understanding of Computational Thinking for 21st-century professional teacher candidates in terms of 4 CT foundations are categorized as "very high". Based on the description of the student's answers, it was also concluded that the CT foundation is indeed the basis for thought processes in solving problems. It is the advantage of Computational Thinking.